Efficient light harvesting anionic heptamethine cyanine-[60] and [70]fullerene hybrids - Villegas, Carmen; Krokos, Evangelos; Bouit, Pierre-Antoine; Delgado, Juan Luis; Guldi, Dirk Michael; Martin, Nazario (Energy and Environmental Science, 2011)
New anionic fullerene-heptamethine conjugates absorbing as far as 900 nm have been synthesized and fully characterized by physicochemical means. In terms of electron transfer, we have succeeded in realizing the rarely occurring scenario of a charge transfer commencing with a higher excited state. Kinetic studies reveal that charge separation and charge recombination dynamics occur in the normal and inverted Marcus region, respectively. © 2011 The Royal Society of Chemistry.